Recurrent Cough and Expectoration for 10 Years: A Case Report. (April 2019) - Huang, Ting; Li, Caihong; Liu, Daishun
Rationale . Most cases of cystic fibrosis occur in Europe, with only a few occurring in Asia. Pulmonary cystic fibrosis is not a rare disease, but in children it is a potentially life-threatening condition. Children suffering from pulmonary cystic fibrosis rarely survive to adulthood, and responses to treatment are generally poor. The most common cause of cystic fibrosis is a genetic mutation on chromosome 7. Patient concerns. A 15-year-old boy with healthy parents suffered from a recurrent cough and expectoration for nearly 10 years. Six years previously, a definitive diagnosis of pulmonary cystic fibrosis and hepatic cirrhosis was made at the Beijing Children's Hospital. The first occurrence of hematemesis occurred 1 year ago. The main symptoms, which caused this period of hospitalization, were cough, expectoration, and hematemesis. Diagnoses. The underlying cause was finally determined to be the cystic fibrosis transmembrane conductance regulator gene (p.G970D). After genetic and sweat testing performed at the Beijing Children's Hospital in 2012, a definitive diagnosis of cystic fibrosis was made. Interventions. The patient was administered hemostatic treatment, antibiotics, and cough relief and sputum reduction therapy. Outcomes. The patient's condition rapidly improved and continued to remain stable, though future relapse is possible following respiratory tract infections. Lessons. This case indicates that in the case of any child that presents a recurrent cryptogenic cough and expectoration, whether accompanied by hematemesis or not, pulmonary cystic fibrosis should be considered. In order to determine underlying causes and prepare for cystic fibrosis transmembrane conductance regulator modulator therapy, genetic and sweat testing are recommended to be conducted if available.